2023
DOI: 10.3390/pathogens12020256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Phylogenetic Analysis of Riemerella anatipestifer in Poultry and Wild Geese in Poland

Abstract: Riemerella anatipestifer (RA) is one of the most relevant bacterial pathogens of commercial waterfowl from clinical and economic points of view. Our study aimed to evaluate the prevalence of RA infection in different types of commercial poultry in Poland and verify the potential role of wild geese as vectors of this pathogen. We tested a total of 126 poultry flocks, including geese (N = 20), ducks (N = 42), turkeys (N = 64) and 19 wild geese, including greater white-fronted geese (N = 9), greylag geese (N = 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Riemerella anatipestifer (RA), formerly known as Pasteurella anatipestifer, is a Gramnegative bacterium from the Flavobacteriaceae family that is considered one of the most economically impactful infectious diseases affecting domestic fowl species worldwide. It mainly infects ducklings and contributes to strain-dependent mortality and morbidity rates of up to 90% and 100%, respectively, in infected ducks or stunted growth in convalescent birds [4][5][6]. RA infection can be acute or chronic, with acute infection being more common in ducks younger than 8 weeks of age [7].…”
Section: Introductionmentioning
confidence: 99%
“…Riemerella anatipestifer (RA), formerly known as Pasteurella anatipestifer, is a Gramnegative bacterium from the Flavobacteriaceae family that is considered one of the most economically impactful infectious diseases affecting domestic fowl species worldwide. It mainly infects ducklings and contributes to strain-dependent mortality and morbidity rates of up to 90% and 100%, respectively, in infected ducks or stunted growth in convalescent birds [4][5][6]. RA infection can be acute or chronic, with acute infection being more common in ducks younger than 8 weeks of age [7].…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of the strains are resistant to aminoglicosides and antibiotics from the polymyxin group [2,11]. It can be observed that the number of manuscripts describing R. anatipestifer infections in European countries has increased in the last two decades [1,10,[13][14][15][16]. The number of poultry farms in Poland has been gradually increasing in recent decades.…”
Section: Introductionmentioning
confidence: 99%